2003
DOI: 10.1161/01.hyp.0000082807.71659.4c
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Fenfluramine-Evoked Prolactin Secretion in Hypertensive Rats

Abstract: Abstract-Plasma prolactin (PRL) levels after acute administration of fenfluramine (FEN) have been used as a probe of brain serotonin activity. FEN-evoked increases in PRL levels inversely correlate with arterial blood pressure (ABP) in humans (Muldoon et al. Hypertension. 1998;32:972-975), thereby suggesting that brain serotonin activity may be reduced in hypertension. The present study sought to determine whether the relation between FEN-evoked PRL levels and ABP was present in two rat models of hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…In this study, it was evidenced that prolactin liberation induced by fenfluramine was correlated inversely with the blood pressure, in white Caucasian individuals suggesting a role of the central 5-HTergic system in the pathogeny of hypertension. The same authors demonstrated a lower prolactin secretory response in SHR rats injected with fenfluramine (Stocker et al 2003).…”
Section: Hypertensionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, it was evidenced that prolactin liberation induced by fenfluramine was correlated inversely with the blood pressure, in white Caucasian individuals suggesting a role of the central 5-HTergic system in the pathogeny of hypertension. The same authors demonstrated a lower prolactin secretory response in SHR rats injected with fenfluramine (Stocker et al 2003).…”
Section: Hypertensionmentioning
confidence: 77%
“…It is tempting to compare our experimental model, at least partially, with the functional condition of the spontaneously hypertensive rats (SHR). SHR rats develop an intense sodium appetite associated with increased angiotensinergic sensitivity in forebrain loci related with the cardiocirculatory and hydroelectrolytic homeostasis (Stocker et al 2003). It is noteworthy that these alterations have been concomitant with a defi cit in the 5-HT turnover in forebrain sites.…”
Section: Lesions Of the Midbrain Raphe Nuclei Brain 5-ht Depletion Amentioning
confidence: 99%
“…Within the brain serotonergic responsivity in the hypothalamic-pituitary axis, as assessed by standard fenfluramine challenge, has been found to covary inversely with resting blood pressure in humans 1 and is attenuated in spontaneously hypertensive rats, relative to normotensive controls. 27 In this regard, the brainstem nuclei involved in BP regulation receive projections from serotonergic neurons, and the central application of serotonin and serotonergic drugs have well-documented acute effects on sympathetic nervous activity, vasopressin release and arterial BP. 7,8 The vasoconstrictve and BPelevating effects of serotonin, both peripherally and centrally, appear to be mediated by 5-HT 2A receptors, whereas 5-HT 1A receptor activation results in sympathoinhibition and vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…G 284 (27) 763 (73) 589 (56) 458 (44) 215 (21) 832 (79) A 178 (23) 603 (77) 403 (52) 378 (48) 121 (15) 660 ( (24) 845 (76) 594 (54) 513 (46) 186 (17) 921 (83) T 224 (29) 537 (71) 412 (54) 349 (46) 162 (22) 599 ( …”
Section: Allelic Distribution −1438unclassified
“…42 Central 5-HT also regulates sleep, and various sleep disturbances may predispose to atherosclerosis. 43,44 Neuroanatomic and neuropharmacologic studies indicate that CNS 5HT modulates sympathetic and parasympathetic outflow affecting heart rate and blood pressure, 45,46 as well as glucose and energy homeostasis. 47,48 Therefore, the influence of CNS serotonergic circuits on autonomic activity could affect atherosclerosis via several internal mechanisms.…”
Section: Discussionmentioning
confidence: 99%